Gemogenovatucel-T (Vigil) immunotherapy as maintenance in frontline stage III/IV ovarian cancer (VITAL): a randomised, double-blind, placebo-controlled, phase 2b trial. Issue 12 (December 2020) - Rocconi, Rodney P; Grosen, Elizabeth A; Ghamande, Sharad A; Chan, John K; Barve, Minal A; Oh, Jonathan; Tewari, Devansu; Morris, Peter C; Stevens, Erin E; Bottsford-Miller, Justin N; Tang, Min; Aaron, Phylicia; et al.
Summary: Background: Gemogenovatucel-T is an autologous tumour cell vaccine manufactured from harvested tumour tissue, which specifically reduces expression of furin and downstream TGF-β1 and TGF-β2. The aim of this study was to determine the safety and efficacy of gemogenovatucel-T in front-line ovarian cancer maintenance. Methods: This randomised, double-blind, placebo-controlled, phase 2b trial involved 25 hospitals in the USA. Women aged 18 years and older with stage III/IV high-grade serous, endometrioid, or clear cell ovarian cancer in clinical complete response after a combination of surgery and five to eight cycles of chemotherapy involving carboplatin and paclitaxel, and an Eastern Cooperative Oncology Group status of 0 or 1 were eligible for inclusion in the study. Patients were randomly assigned (1:1) to gemogenovatucel-T or placebo by an independent third party interactive response system after successful screening using randomly permuted block sizes of two and four and stratified by extent of surgical cytoreduction and neoadjuvant versus adjuvant chemotherapy. Gemogenovatucel-T (1 × 10 7 cells per injection) or placebo was administered intradermally (one per month) for a minimum of four and up to 12 doses. Patients, investigators, and clinical staff were masked to patient allocation until after statistical analysis. The primary endpoint was recurrence-free survival, analysed in the per-protocol population. All patients who received at least one dose of gemogenovatucel-T were included in the safety analysis. The study is registered with ClinicalTrials.gov, NCT02346747 . Findings: Between Feb 11, 2015, and March 2, 2017, 310 patients consented to the study at 22 sites. 217 were excluded. 91 patients received gemogenovatucel-T (n=47) or placebo (n=44) and were analysed for safety and efficacy. The median follow-up from first dose of gemogenovatucel-T was 40·0 months (IQR 35·0–44·8) and from first dose of placebo was 39·8 months (35·5–44·6). Recurrence-free survival was 11·5 months (95% CI 7·5–not reached) for patients assigned to gemogenovatucel-T versus 8·4 months (7·9–15·5) for patients assigned to placebo (HR 0·69, 90% CI 0·44–1·07; one-sided p=0·078). Gemogenovatucel-T resulted in no grade 3 or 4 toxic effects. Two patients in the placebo group had five grade 3 toxic events, including arthralgia, bone pain, generalised muscle weakness, syncope, and dyspnea. Seven patients (four in the placebo group and three in the gemogenovatucel-T group) had 11 serious adverse events. No treatment-related deaths were reported in either of the groups. Interpretation: Front-line use of gemogenovatucel-T immunotherapy as maintenance was well tolerated but the primary endpoint was not met. Further investigation of gemogenovatucel-T in patients stratified by BRCA mutation status is warranted. Funding: Gradalis.